Periprosthetic infection risks and predictive value of C-reactive protein / albumin ratio for total joint arthroplasty: Periprosthetic infection risks and value of C-reactive protein / albumin ratio - Yigit, Şeyhmus; Akar, Mehmet Sait; Şahin, Mehmet Akif; Arslan, Hüseyin (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: There are no gold standard markers to estimate the risk of developing periprosthetic infections. Our aim is to compare the risks of periprosthetic infection in patients with THA and THA and to investigate the predictive significance of the CRP / albumin ratio.Methods: This is a retrospective study containing data from 241 osteoarthritis patients and 19 patients with periprosthetic infections who underwent TKA and THA in our hospital from January 2014 to January 2019.12 risk factors(CRP/ albumin, albumin, CRP, age, gender, BMI, DM, ASA, nasal culture, urine culture, hospital stay, operation time) were analyzed.Results: In the binary logistic regression model and multivariate regression analysis, the rate of CRP / albumin was 17.161 times higher than the patients with ≤0.16 cut-off value. (CRP / albumin ratio (odds ratio (OR) = 17.16, 95% CI: 1.55-189.03, P: 0.02). High BMI increased the risk of periprosthetic infection 1.3 times. Nasal bacterial colonization (OR = 0.99, 95% CI: 0.868-1.38, P: 0.7) and bacterium in urine (OR = 0.502, 95% CI: 0.07-3.598, P: 0.703) did not pose a significant risk for periprosthetic infection.Conclusion: According to our findings, the CRP / albumin ratio has a more prognostic capacity than other risks in determining the risk of periprosthetic infection for total joint arthroplasty. CRP / albumin ratio is a cheap and easy to apply marker. Routine urine and nasal bacteria screening is not required before total joint arthroplasty.